O útero biopolítico: a resistência das vítimas do Essure, da Bayer - Carvalho, Miriam Kenia de (2023)
This thesis aims to investigate, based on the Corpomedia Theory (KATZ; GREINER, 2001), the group of bodies with uterus that was summoned by the pharmacopornography industry apparatus, in Brazil, for the implantation of the Essure device from Bayer. Propagated as a modern sterilization, a permanent contraception, with no cut, no pain, no need to be absent from work, performed in a 20-minute procedure, it captured those who were in line to get a sterilization in the public health system. The goal is to denounce that the arguments were a fallacy, Essure caused diseases, the deceived women were discarded by the system, and the repair of these bodies, denied at first, represents, paradoxically, the mutilation of the uterus. In the first part, the research denounces the strategies used to capture these bodies. In the second part, it presents the resistance organized by the global network Victims of Essure. This resistance causes fissures in the established pharmacopornographic regime (PRECIADO, 2018), with reflections on public policies. The research also reveals the perversity of gender hegemony (RAGO, 1997; VIEIRA, 2002; DESPENTES, 2016; GEABRA, 2019) that holds the body with a uterus exclusively responsible for contraception and other crossings of biopolitical inequality (ROSE, 2013) in the control of subjectivity (FOUCAULT, 2014). However, this corpomedia, which at first only supported the pharmacopornography, immersed in other information and encounters, towards reparation (MBEMBE, 2020), produces perspectives for bioempowerment (PRECIADO, 2018). The methodology brought together literature review and field research, with the conduct of interviews and the organization of a database with the media communication of the pharmacopornography and the victims